PTU-104 Outcomes Of Increased Dose Of Allopurinol In Ibd Patients Who Developed Hepatotoxicity On Low Azathioprine And Allopurinol Co-therapy Treatment. (9th June 2014) - Pericleous, M; Abdulrehman, A; Bull, C; Mackenzie, G; Stenner, J; Cowan, M; Hillman, G; Ansari, A
Abstract : Introduction: The thiopurines (azathioprine (AZA) and metcaptopurine (6MP)) are established first line therapies for inflammatory bowel disease (IBD). However, when these agents are used at their target dose side effects are common, gastrointestinal intolerance (10–20%) and hepatotoxicity (>10%). 1 These side effects can often be bypassed by using low dose AZA and allopurinol (ALLO) co-therapy (LDAA). The current opinion is that hepatotoxicity is secondary to high red cell methylated metabolites (MMPR/MMP). However, many patients develop hepatotoxicity without high MMP levels .2 We report a series of patients who regardless of low MMP developed hepatotoxicity whilst on allopurinol co-therapy, 3 of which were TPMT heterozygotes. Aim: to determine outcomes of increasing the dose of Allopurinol from 100 to 200 mg in patients with hepatotoxicity to LDAA. Methods: Patient records and our IBD database were searched for patients on LDAA who developed hepatotoxicity whilst on LDAA (100 mg of ALLO). Liver function tests (LFTs), liver screen, ultrasound results and clinical outcomes were determined. Results: From the 2500 patients with IBD locally, 600 were exposed to thiopurines and 300 were on LDAA. Nine patients had sustained hepatotoxicity, 3 were TPMT heterozygotes. Seven of these patients responded fully to increased dose of ALLO to 200mg. Two had a suboptimal response (1 had PSC as a potential cause). All patients had asymptomatic abnormalities of LFTS, negative chronic liver screen apart from 2 who had ultrasound proven fatty liver disease without abnormal LFTs prior to LDAA. We observed that all patients had improvements in their LFTs, whilst 7 had complete correction of abnormal AST, ALP and bilirubin. Median time for treatment was 24 months (range 12–48 months), with full response to therapy in all 7 patients. Conclusion: This is the first series which reports improvement of LFTs by increasing ALLO dose for patients on LDAA. This subgroup of patients were unlikely to have high MMPR as 3 of them were TPMT heterozygotes and all were on LDAA therapy, therefore a different mechanism, of hepatotoxicity is proposed (Figure 1 ). It is possible that reactive oxygen species generated from the oxidation of metcaptopurine are responsible, and this can be further improved by adjusting the dose of ALLO. Further studies are required. References: Bastida G, Nos P, Aguas M, et al . Incidence, risk factors and clinical course of thiopurine-induced liver injury in patients with inflammatory bowel disease. Aliment Pharmacol Ther 2005;22:775–82 Shaye OA, Yadegari M, Abreu MT, et al. Hepatotoxicity of 6-mercaptopurine (6-MP) and Azathioprine (AZA) in adult IBD patients. Am J Gastroenterol 2007;102:2488–94 Disclosure of Interest: None Declared.